2015
DOI: 10.3892/etm.2015.2457
|View full text |Cite
|
Sign up to set email alerts
|

Nonadherent culture method downregulates stem cell antigen-1 expression in mouse bone marrow mesenchymal stem cells

Abstract: Abstract. Mesenchymal stem cells (MSCs) are primarily isolated by their adherence to plastic and their in vitro growth characteristics. Expansion of these cells from an adherent culture is the only method to obtain a sufficient number of cells for use in clinical practice and research. However, little is known with regard to the effect of adherence to plastic on the phenotype of the cells. In the present study, bone marrow CD45 -CD31 -CD44 -stem cell antigen (Sca)-1 + MSCs were sorted by flow cytometry and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…It is also possible that HSC may be present, but after for 3–4 weeks of culture, attain a different phenotype. In particular, culturing of Lin - Sca-1 + c-Kit + cells over stroma may lead to loss of the Sca-1 marker, a phenomenon reported previously for mesenchymal stem cells in vitro (Deng et al, 2015). Previously we reported evidence for maintenance of low numbers of HSPC in spleen longterm stromal cultures through ability to induce hematopoietic reconstitution in irradiated host mice (O’Neill et al, 2014).…”
Section: Resultsmentioning
confidence: 58%
“…It is also possible that HSC may be present, but after for 3–4 weeks of culture, attain a different phenotype. In particular, culturing of Lin - Sca-1 + c-Kit + cells over stroma may lead to loss of the Sca-1 marker, a phenomenon reported previously for mesenchymal stem cells in vitro (Deng et al, 2015). Previously we reported evidence for maintenance of low numbers of HSPC in spleen longterm stromal cultures through ability to induce hematopoietic reconstitution in irradiated host mice (O’Neill et al, 2014).…”
Section: Resultsmentioning
confidence: 58%
“…The major reason for lacking information about Ly6a in our scRNA-seq data is that we cultured the periosteal cells for a week to acquire enough cells for scRNA-seq. It has been reported that adherent cell culture could downregulate the expression of Ly6a in mesenchymal stem cells (Deng et al 2015). Thus, we chose to label resident Ctsk + Ly6a + cells in vivo with immunofluorescent staining to exhibit their specific distribution in the periosteum of jawbone.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to primary MSCs, cultured MSCs with high levels of CD44 displayed decreased targeting to the bone marrow [13]. Our previous research revealed that stem cell antigen 1 (Sca-1) is expressed at higher levels in adherent cultured mouse MSCs (AC-mMSCs) compared to mMSCs in nonadherent cultures maintained in ultra-low-adherent plates (nonAC-mMSCs) [14]. Sca-1 + mMSCs play a crucial role in improving cardiac function in MI [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research revealed that stem cell antigen 1 (Sca-1) is expressed at higher levels in adherent cultured mouse MSCs (AC-mMSCs) compared to mMSCs in nonadherent cultures maintained in ultra-low-adherent plates (nonAC-mMSCs) [14]. Sca-1 + mMSCs play a crucial role in improving cardiac function in MI [14,15]. Compared with nonadherent cultured human MSCs (nonAC-hMSCs), adherent cultured hMSCs (AC-hMSCs) with high protein expression of caspase-3, caspase-7, and caspase-9 had a marked decrease in cell apoptosis [16].…”
Section: Introductionmentioning
confidence: 99%